2011
DOI: 10.1182/blood-2010-12-324574
|View full text |Cite
|
Sign up to set email alerts
|

The vitronectin-binding function of PAI-1 exacerbates lung fibrosis in mice

Abstract: Plasminogen activator inhibitor-1 (PAI-1) is increased in the lungs of patients with pulmonary fibrosis, and animal studies have shown that experimental manipulations of PAI-1 levels directly influence the extent of scarring that follows lung injury. PAI-1 has 2 known properties that could potentiate fibrosis, namely an antiprotease activity that inhibits the generation of plasmin, and a vitronectin-binding function that interferes with cell adhesion to this extracellular matrix protein. To determine the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…Studies in lung (70) and liver (180) fibrosis models have shown that the profibrotic effect of PAI-1 depends on its inhibition of tPA or uPA and support the notion that impairment of normal extracellular collagen breakdown pathways can lead to pathologic fibrosis. However, another recent study on PAI-1 Ϫ/Ϫ mice that had been transgenically engineered to selectively express PAI-1 protein constructs including or lacking PAI-1's antiprotease domain concluded that the major contribution of PAI-1 to fibrogenesis rests not on its antiproteolytic function but its ability to bind vitronectin (30). PAI-1 is clearly important in the development and resolution of fibrosis.…”
Section: Extracellular Pathway Of Collagen Degradationmentioning
confidence: 99%
“…Studies in lung (70) and liver (180) fibrosis models have shown that the profibrotic effect of PAI-1 depends on its inhibition of tPA or uPA and support the notion that impairment of normal extracellular collagen breakdown pathways can lead to pathologic fibrosis. However, another recent study on PAI-1 Ϫ/Ϫ mice that had been transgenically engineered to selectively express PAI-1 protein constructs including or lacking PAI-1's antiprotease domain concluded that the major contribution of PAI-1 to fibrogenesis rests not on its antiproteolytic function but its ability to bind vitronectin (30). PAI-1 is clearly important in the development and resolution of fibrosis.…”
Section: Extracellular Pathway Of Collagen Degradationmentioning
confidence: 99%
“…Plasminogen activator inhibitor (PAI)-1 concentrations in cell supernatants were measured using a carboxylated microsphere-based ELISA (Luminex) (8).…”
Section: Pai-1 Concentrationsmentioning
confidence: 99%
“…There exist many plausible mechanisms by which PAI-1 might influence this monocyte recruitment. For example, PAI-1 may enhance the transendothelial migration of Ly6C high monocytes across the pulmonary vasculature (perhaps through its vitronectinbinding function) [42]. Alternatively, PAI-1 may alter the expression or recognition of monocyte/macrophage chemotactic factors (ie CCL2 or CCL7).…”
Section: Discussionmentioning
confidence: 99%
“…This induction of PAI-1 expression mimics the elevated levels of intrapulmonary PAI-1 observed in patients with pulmonary fibrosis of varying aetiologies [14][15][16]18]. PAI-1 production is also increased in the lung following bleomycin-mediated injury [19,20,[22][23][24][25][26]42]. To determine whether the enhanced PAI-1 production following type II AEC injury was required for fibro-genesis, we generated transgenic mice that expressed human DTR on their type II AECs and were deficient in PAI-1.…”
Section: Discussionmentioning
confidence: 99%